(untitled) (Vietnam Journal of Community Medicine, 2022)
A cross-sectional study was based on an online survey of over 409 students studying at Hanoi Medical University to show students’ adaptability to changes in teaching and learning methods in the COVID-19 pandemic and students’ evaluations on those methods. The results show that most of the students at Hanoi Medical University are able to respond to changes in learning methods during the COVID-19 pandemic although their adaptation has not been at the perfect level yet, it will be improved in the future. Students have expectations about combining online teaching and learning with the university’s training system.